IMPROVED FIRE-PROOF INSTALLATION SECURITY TECHNOLOGY - Dicky Lesmana (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
In this study conducted a discussion of electrical installation of buildings as electrical equipment assemblies in buildings related to each other, to meet certain purposes or intentions and have coordinated characteristics, what is already stated in the General Requirements of Electrical Installation (PUIL 2000). The purpose and purpose of the electrical installation is for the business of electrical installations to be held properly, to ensure human safety from the dangers of electric shock, the safety of electrical installations and their equipment, the security of buildings and their contents from fires caused by electricity, and environmental protection. Things that have been considered trivial by the community, unwittingly have been the trigger for the high number of fire cases. Fires can occur if there are three elements, namely flammable materials, oxygen and sparks. Short circuit of electric current or (electrical short circuit) that causes flame catches to flammable materials, is still the trigger for high fire rates.